Chromosome 5 harbors two independent deletion hotspots at 5q13 and 5q21 that characterize biologically different subsets of aggressive prostate cancer. Issue 3 (24th October 2020) - Möller, Katharina; Kluth, Martina; Ahmed, Malik; Burkhardt, Lia; Möller‐Koop, Christina; Büscheck, Franziska; Weidemann, Sören; Tsourlakis, Maria‐Christina; Minner, Sarah; Heinzer, Hans; Huland, Hartwig; Graefen, Markus; et al.
Abstract: Deletion of chromosome 5q is common in prostate cancer and is linked to aggressive disease. Most previous studies focused on 5q21 where CHD1 is located, but deletion of mapping studies has identified a second deletion hotspot at 5q13. To clarify the prevalence and clinical relevance of 5q13 deletions and to determine the relative importance of 5q13 and 5q21 abnormalities, a tissue microarray containing samples from 12 427 prostate cancers was analyzed by fluorescence in situ hybridization. Deletion of 5q13 and 5q21 was found in 13.5% and 10%, respectively, of 7932 successfully analyzed cancers. Deletion was restricted to 5q13 in 49.4% and to 5q21 in 32.0% of cancers with a 5q deletion. Only 18.6% of 5q‐deleted cancers had deletions of both loci. Both 5q13 and 5q21 deletions were significantly linked to advanced tumor stage, high Gleason grade, nodal metastasis and early biochemical recurrence ( P < .005 each). Cancers with co‐deletion of 5q13 and 5q21 had a worse prognosis than cancers with isolated 5q13 or 5q21 deletion ( P = .0080). Comparison with TMPRSS2:ERG fusion status revealed that 5q21 deletions were tightly linked to ERG negativity ( P < .0001) while 5q13 deletions were unrelated to the ERG status. In summary, 5q13 deletion and 5q21 deletion are common, but independent genomic alterations with different functional effects lead to aggressive prostate cancer. Abstract : What's new? Deletion of chromosome 5q is common in prostate cancer and is linked to aggressive disease. However, most studies have focused on 5q21 where CHD1, a gene required for maintenance of androgen receptor signaling, is located. Chromosome 5q13 has also been shown to harbor a small interstitial deletion, whose clinical relevance in prostate cancer remains unknown. The hereby presented gene copy number analysis of more than 12, 000 prostate cancers reveals that 5q13 deletion is distinct from the well‐known 5q21 deletion, associates with TMPRSS2:ERG fusion type cancers, and characterises a patient set with aggressive tumor features and poor prognosis.